2016
DOI: 10.1371/journal.pone.0164733
|View full text |Cite
|
Sign up to set email alerts
|

Is Decoupling GDP Growth from Environmental Impact Possible?

Abstract: The argument that human society can decouple economic growth—defined as growth in Gross Domestic Product (GDP)—from growth in environmental impacts is appealing. If such decoupling is possible, it means that GDP growth is a sustainable societal goal. Here we show that the decoupling concept can be interpreted using an easily understood model of economic growth and environmental impact. The simple model is compared to historical data and modelled projections to demonstrate that growth in GDP ultimately cannot b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
225
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 368 publications
(236 citation statements)
references
References 27 publications
2
225
1
8
Order By: Relevance
“…Moreover, the Hatfield‐Dodds et al (2015) results apply only to the short term. Ward et al () have demonstrated that the same model extrapolated into the longer term shows that material footprint begins to rise again after 2050, approaching the rate of GDP growth. The reason is that resource efficiency improvements eventually approach physical limits, after which growth drives resource use back up.…”
Section: Is Goal 8 Compatible With Sustainable Resource Use?mentioning
confidence: 95%
“…Moreover, the Hatfield‐Dodds et al (2015) results apply only to the short term. Ward et al () have demonstrated that the same model extrapolated into the longer term shows that material footprint begins to rise again after 2050, approaching the rate of GDP growth. The reason is that resource efficiency improvements eventually approach physical limits, after which growth drives resource use back up.…”
Section: Is Goal 8 Compatible With Sustainable Resource Use?mentioning
confidence: 95%
“…Burton, 2015Burton, , 2016bIsenhour, 2016;Isenhour & Feng, 2016;Jackson, 2011;Ward et al, 2016). As noted earlier, there is evidence that absolute decoupling at the global level has not yet occurred for important inflows of energy and matter; only (limited) relative decoupling has been documented thus far (Energy Information Administration [EIA], 2014; Haas, Krausmann, Wiedenhofer, & Heinz, 2015;Sustainable Europe Research Institute, 2013), and even this is questionable given the widespread tendency for environmental damage to 'leak' outside the area of assessment (Isenhour, 2016;Isenhour & Feng, 2016;Ward et al, 2016). The same is true for the decoupling of outflows of waste and emissions, using carbon dioxide (CO 2 ) emissions as a proxy for other outflows (EIA, 2104;Mitchell, 2012;in Rammelt & Crisp, 2014).…”
Section: Defying the Laws Of Naturementioning
confidence: 99%
“…In short, a growth-based economy will always demand growing energy inputs (Ward et al, 2016). As Boulding cautioned long ago, 'In regard to the energy system there is, unfortunately, no escape from the grim Second Law of Thermodynamics ' (1966, p. 6).…”
Section: Defying the Laws Of Naturementioning
confidence: 99%
See 1 more Smart Citation
“…However, closer scrutiny has found that this too is not a bottomless well. 8 What is more, indications are that even replacing fossil fuels with renewables is not a viable option for maintaining current levels of consumption. 9 It seems we must instead nd solutions that involve reductions in our collective energy use.…”
Section: The Future Of Ef Ciencymentioning
confidence: 99%